Challenges Facing the Adoption and Implementation of Weather Indexed Insurance by Insurance Firms - Kajwang, Ben (Journal of Agricultural Policy, 2022)
Purpose: The study assessed the challenges facing the adoption and implementation of weather indexed insurance by insurance firms Methodology: This was accomplished through the use of a desktop literature review. The use of Google Scholar was utilized in order to locate seminal references and journal articles that were pertinent to the study. In order to meet the inclusion criteria, the papers had to be no more than ten years old. Findings: Using a certain weather parameter, a specific weather station, and a predetermined length of time, Weather Index Insurance is calculated. To avoid crop losses, the insurance might be constructed to cover against index realizations that are predicted to be too high or low. Pilots and feasibility studies have indicated that while the weather index product appears to be a boon, there are numerous hurdles or downsides to weather index products. Because of this, we set out to find out what obstacles insurance companies may face in implementing weather-indexed insurance. Index insurance's biggest flaw is its exposure to basis risk. In addition, weather-related risks exhibit characteristics that frequently contravene classical insurance rules. Drought and other slow-developing meteorological hazards, such as floods, can have a systemic effect since they are regionally connected. As a result, actuarial ratemaking becomes more challenging because of the increased volatility of meteorological variables and non-stationary loss distributions. Third, a lack of yield and weather data makes it difficult to estimate loss distributions accurately. Some farmers may not comprehend weather index insurance and hence not buy it, and a significant number of farmers may also require a subsidy if they want to get weather insurance. Unique contribution of theory, practice and policy: Crop insurance companies can benefit from approaches like time diversification, local test procedures, and the addition of expert knowledge to observational data, as well as mechanisms like supporting insurance market development as a means of facilitating adaptation. In addition, better training on weather index insurance and regular communication are required.